Pedagogical Framework to Fulfill and Improve the Understanding of Capstone Design Engineering Among STEM Graduates – A Mini Review - Pauzi, Aziah; Kasim, Farizul Hafiz; Zakaria, Zaki Yamani (Journal of Education Technology, 2024)
In the challenging 21st century learning environment, there is an increasing need to ensure that engineers can solve new and difficult engineering challenges. So it is important to update engineering education to produce engineers who can solve problems and work in today’s environment. The problem underlying this research is the existence of weaknesses in the learning of design project courses or integrated design engineering courses in chemical engineering and it is very important to provide support for student understanding and achievement of program outcomes. This study aims to shape, build and assess teaching and learning models for chemical engineering design projects by exploring teaching pedagogy. This research is a basic research that uses a design and development approach based on the ADDIE model. Therefore, it is highly hoped that this investigation can provide input on more effective learning models. The population of this study was final year students at the Faculty of Chemical Engineering & Technology, and 9 expert teaching staff from most universities throughout the country. In conclusion, the application of this model is expected to provide opportunities and guidance to interested parties including lecturers, teachers and students to improve their skills and abilities in solving complex engineering problems in design project courses in the future.